Overview of the Influence of Land Use Change and Sediment Control Structures on Sedimentation in Lake Sentani - Laorens Miehell Ngutra; Mujiati Mujiati; Harmonis Rante; Bernathius Julison; Duha Awaluddin; Dewi Ana Rusim (Publikasi Indonesia, 2024)
Under Presidential Decree No. 60 of 2021, on National Priority Lakes Rescue, Lake Sentani is one of 15 priority lakes to be rescued. In the annex to the President's regulation, it is mentioned to date about 90 tons or ± 5 m/year of sediment entering Lake Sentani with a total count of 62,0679.78 tonnes/year entering lake Sentani, with a storage capacity of 1,782 billion/m3. The water supply of Lake Sentani is obtained from the supply of 14 large and small rivers. With a slope inclination between 0% - 40% of the amount of sediment transported during the rainy season causes the decline in water quality and the high erosion that occurs. This study aims to find out the impact of land-use change and the effect of sediment control buildings on the number of sediments that enter Lake Sentani. From the results of the analysis the impact of land use change before the construction of the sediment control building based on the analysis carried out by the Papua River Regional Hall the known potential sedimentation rate is of 0.6 mm/th whereas the potential sedmentation rate analysed after the existence of the building of the Sediment Controller is of 0.012 mm /year. This indicates a change in the rate of potential Sedimentation entering the lake of sentani affected by the building sediment operator. When it rains with repeated flooding Q20, Q25, Q50 and Q100 years with conditions of 1 (one) sediment control building so that it can be judged to be a very heavy erosion class with land loss of more than 280 tons/ha/years with a potential sedimentation rate thickness between 2.55 mm/years to 2.85mm/years.